Comparative Analysis Of Brand Equity Between Aqua And Le Minerale Bottled Drinking Water Products - Nurul Ittaqullah (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Competition in the bottled mineral water industry in Indonesia is becoming increasingly intense along with the growing public awareness of the importance of consuming safe and healthy drinking water. AQUA, as a pioneer and market leader, faces direct competition from Le Minerale, which has emerged as a challenger brand positioned around product quality and water purity. This study aims to analyze and compare the brand equity of AQUA and Le Minerale bottled mineral water products based on four main dimensions: brand awareness, brand association, perceived quality, and brand loyalty. The population of this study consisted of students at Halu Oleo University who consume bottled mineral water. The sample consisted of 80 respondents determined using the Hair et al. approach. Data were collected through questionnaires using a Likert scale. The data analysis techniques employed were descriptive statistics and the Independent Sample T-Test using SPSS software. The results showed significant differences in brand awareness, brand association, and perceived quality between AQUA and Le Minerale. However, no significant difference was found in the brand loyalty dimension. These findings indicate that although AQUA excels in brand recognition and perceived quality, both brands have successfully established relatively comparable consumer loyalty among university students